2006
DOI: 10.1007/s10482-006-9110-x
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of mtDNA RFLP variability among Aspergillus tubingensis isolates

Abstract: Aspergillus tubingensis isolates collected from distant geographic areas were earlier classified into six groups on the basis of the mtDNA RFLP variability they exhibited (mtDNA types 2a-2f). In the present work, we investigated the reason for the intraspecific mtDNA variability and we describe here how this fungus, with a relatively small mitochondrial genome, can display intraspecific polymorphism due to intron acquisition and also sporadic point mutations affecting the recognition motifs of the restriction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 28 publications
2
10
0
Order By: Relevance
“…Phylogenetic study supports intraspecific variability found within A. tubingensis by other authors (Varga et al. , 1993, 1994; Juhász et al. , 2004, 2007).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Phylogenetic study supports intraspecific variability found within A. tubingensis by other authors (Varga et al. , 1993, 1994; Juhász et al. , 2004, 2007).…”
Section: Discussionsupporting
confidence: 89%
“…Aspergillus tubingensis species have become a greater focus of attention since its high incidence on grapes and OTA-producing ability were described (Medina et al, 2005;Battilani et al, 2006;Perrone et al, 2006a,b). Furthermore, intraspecific variability has been reported within A. tubingensis species (Varga et al, 1993(Varga et al, , 1994Juha´sz et al, 2004Juha´sz et al, , 2007Martı´nez-Culebras & Ramo´n, 2007). Accurate identification of different A. tubingensis isolates might be important to determining toxicological risks because the toxic profile of each isolate could differ.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, interspecific length variability of mtDNAs among filamentous fungi, like Aspergillus nidulans, Podospora anserina, Neurospora crassa and their relatives are based on the altered intron content of genes and the optional presence of free-standing intronic ORFs (Earl et al, 1981;Collins & Lambowitz, 1983;Koll et al, 1996;Belcour et al, 1997). The same is the reason for the intraspecific mtDNA polymorphism, which seems to be a very typical feature of the imperfect black Aspergilli, like Aspergillus carbonarius (Kevei et al, 1996;Hamari et al, 1999), Aspergillus japonicus , A. niger (Hamari et al, 2003) and A. tubingensis (Juhász et al, 2007). Mitochondrial introns are considered as mobile elements due to their 'parasitic' ORFs, which provide the introns with mobile characteristics (Lambowitz & Belfort, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…The mitochondrial genome is an attractive molecule for application in fungal taxonomy and systematics, with a rapid rate of evolution and limited genetic recombination [38,39]. For Aspergillus , both specific and intraspecific level comparisons have been described [40,41]. Considering the high copy number per cell, mitochondrial DNA (mtDNA) is also easily amplifiable by PCR and appropriate for characterization through RFLP analysis.…”
Section: Discussionmentioning
confidence: 99%